Knowledge and Readiness Towards Genomic Nursing among Nursing Students at a Select Nursing College in Mangalore - Ann Mariya T; An Mariya S; Anjali R; Anitta ES; Anjana J; Anit TT; Roslin S; Bibi Augustin (RGUHS Journal of Nursing Sciences)
Background and aim The process of investigating analysing diagnosing treating and recommending preventive measures for human health and disease has been revolutionized by genetics. A thorough understanding of genomics has paved the way for individualized methods of providing health care that makes use of a persons environment and genes to help treat diagnose or prevent disease. Being the backbone of the healthcare team nurses need to be prepared to keep up with advances in genomics and the resulting transformation of the healthcare industry. The aim of the present research was to assess the knowledge and readiness in genomic nursing practice.Methods Using a convenient sampling 148 third- and fourth-year BSc nursing students were recruited for this cross-sectional descriptive design study. A standardized knowledge questionnaire on genomic nursing and a readiness rating scale was used to gather data. Both descriptive and inferential statistics were applied to analyze the data.Results The results revealed that more than half of the respondents 99 67 had poor 45 30 had satisfactory and 4 3 had a good level of knowledge regarding genomic nursing. Majority of the respondents 78 115 reported non-readiness in practicing genomic nursing whereas only 22 33 were ready to practice genomic nursing. There was no significant correlation between baseline variables and knowledge scores regarding genomic nursing at 0.05 level of significance.Conclusion The results of the current study revealed that among 148 participants third and final year BSc nursing students majority of students lacked knowledge regarding genomic nursing. With regards to confidence in practicing genomic nursing majority were somewhat confident only a few students were very confident and some were not at all confident. The study recommends a greater focus on genomic concepts as inclusion of genomics in health care can revolutionize the treatment.